Tobacco imagery on prime time UK television - Lyons, Ailsa; McNeill, Ann; Britton, John (BMJ Publishing Group, 2013)
Background: Smoking in ﬁlms is a common and well documented cause of youth smoking experimentation and uptake and hence a signiﬁcant health hazard. The extent of exposure of young people to tobacco imagery in television programming has to date been far less investigated. We have therefore measured the extent to which tobacco content occurs in prime time UK television, and estimated exposure of UK youth. Methods: The occurrence of tobacco, categorised as actual tobacco use, implied tobacco use, tobacco paraphernalia, other reference to tobacco, tobacco brand appearances or any of these, occurring in all prime time broadcasting on the ﬁve most popularly viewed UK television stations during 3 separate weeks in 2010 were measured by 1-minute interval coding. Youth exposure to tobacco content in the UK was estimated using media viewing ﬁgures. Findings: Actual tobacco use, predominantly cigarette smoking, occurred in 73 of 613 (12%) programmes, particularly in feature ﬁlms and reality TV. Brand appearances were rare, occurring in only 18 programmes, of which 12 were news or other factual genres, and 6 were episodes of the same British soap opera. Tobacco occurred with similar frequency before as after 21:00, the UK watershed for programmes suitable for youth. The estimated number of incidences of exposure of the audience aged less than 18 years for any tobacco, actual tobacco use and tobacco branding were 59 million, 16 million and 3 million, respectively on average per week. Conclusions: Television programming is a source of signiﬁcant exposure of youth to tobacco imagery, before and after the watershed. Tobacco branding is particularly common in Coronation Street, a soap opera popular among youth audiences. More stringent controls on tobacco in prime time television therefore have the potential to reduce the uptake of youth smoking in the UK.